18-(3x-5)=5(x-1)-6

Simple and best practice solution for 18-(3x-5)=5(x-1)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18-(3x-5)=5(x-1)-6 equation:



18-(3x-5)=5(x-1)-6
We move all terms to the left:
18-(3x-5)-(5(x-1)-6)=0
We get rid of parentheses
-3x-(5(x-1)-6)+5+18=0
We calculate terms in parentheses: -(5(x-1)-6), so:
5(x-1)-6
We multiply parentheses
5x-5-6
We add all the numbers together, and all the variables
5x-11
Back to the equation:
-(5x-11)
We add all the numbers together, and all the variables
-3x-(5x-11)+23=0
We get rid of parentheses
-3x-5x+11+23=0
We add all the numbers together, and all the variables
-8x+34=0
We move all terms containing x to the left, all other terms to the right
-8x=-34
x=-34/-8
x=4+1/4

See similar equations:

| 2w+2(3w-5)=82 | | 4=-7x+8x | | X/3-2x+1/2=5/6 | | (2x+1)^2-(-x+1)^2=(x-1)(3x+2) | | -7p+8p=7 | | 0.02(y-9)+0.18y=0.14y-0.03(10) | | 48-3x=-109-8x | | 3x-5=5x/x-3/x | | -6(v-1)=5v-49 | | -281=1-6(5-6x) | | 10x-21=4x | | 7x-4;x=5 | | 8/9(54-36)+2=-3/4(-40+16x)+90x | | 12x+2=11x-6 | | 3x-5=5x-3/x | | 6(x+2)-4x=2(x-3)+18 | | -7y+23=-2(y-4) | | 2(y+7)=5(3-2y) | | x/9=11/5- | | 15+q#6=-21 | | X+2=x-7 | | 5x-6+3x=x | | 5(1-5x)=-28+2x | | 7x-112=3x+60 | | -8(w-1)=-4w+36 | | 4(2x-7)=6x | | -9x-45-10x-1=35 | | 2x+3=17x | | 2x2=162 | | x/4/2=28 | | 8(y+4)-6y=14 | | 9x-13=10x+8 |

Equations solver categories